Complications related to surgically assisted rapid palatal expansion - VAROL, ALTAN; UĞURLU, FAYSAL; DERGİN, GÜHAN; GARİP, HASAN (ELSEVIER SCIENCE INC, 2015)
Objective. The goals of this retrospective clinical study were to identify surgically assisted rapid palatal expansion (SARPE) complications and assess their incidence, with the aim of informing surgeons and orthodontists of the risks of this widely used procedure before they recommend it to patients. Study Design. Between June 2008 and July 2010, 60 patients (23 women and 37 men) underwent SARPE according to a defined multidisciplinary protocol at the University of Marmara, Istanbul, Turkey. Results. Twelve patients (20%) suffered from nasal bleeding. Of these 12, 2 patients suffered late-onset bleeding beginning on postoperative day 8, and in the other 10, nasal bleeding was insignificant. Three patients reported excessive lacrimation postoperatively. Minor problems related to pain and numbness were all temporary. Conclusions. SARPE procedures have traditionally been reported to be associated with low morbidity, especially in comparison with other orthognathic surgical procedures. However, many complications have been reported.
Keywords: FORT-I OSTEOTOMY; EXTERNAL ROOT RESORPTION; MAXILLARY EXPANSION; ORTHOGNATHIC SURGERY; ORTHODONTIC EXPANSION; MIDPALATAL SUTURE; BLOOD-FLOW; DISTRACTION; EPISTAXIS; REPAIR